Diet‐associated vertically transferred metabolites and risk of asthma, allergy, eczema, and infections in early childhood. Issue 2 (17th February 2023) - Brustad, Nicklas; Olarini, Alessandra; Kim, Min; Chen, Liang; Ali, Mina; Wang, Tingting; Cohen, Arieh S.; Ernst, Madeleine; Hougaard, David; Schoos, Ann‐Marie; Stokholm, Jakob; Bønnelykke, Klaus; et al.
Abstract: Background: Evidence suggests maternal pregnancy dietary intake and nutrition in the early postnatal period to be of importance for the newborn child's health. However, studies investigating diet‐related metabolites transferred from mother to child on disease risk in childhood are lacking. We sought to investigate the influence of vertically transferred metabolites on risk of atopic diseases and infections during preschool age. Methods: In the Danish population‐based COPSAC2010 mother–child cohort, information on 10 diet‐related vertically transferred metabolites from metabolomics profiles of dried blood spots (DBS) at age 2–3 days was analyzed in relation to the risk of childhood asthma, allergy, eczema, and infections using principal component and single metabolite analyses. Results: In 678 children with DBS measurements, a coffee‐related metabolite profile reflected by principal component 1 was inversely associated with risk of asthma (odds ratio (95% CI) 0.78 (0.64; 0.95), p  = .014) and eczema at age 6 years (0.79 (0.65; 0.97), p  = .022). Furthermore, increasing stachydrine (fruit‐related), 3‐carboxy‐4‐methyl‐5‐propyl‐2‐furanpropanoate (fish‐related), and ergothioneine (fruit‐, green vegetables‐, and fish‐related) levels were all significantly associated with reduced risks of infections at age 0–3 years ( p  < .05). Conclusion: This study demonstrates associations between pregnancy diet‐related vertically transferred metabolites measured in children in early life and risk of atopic diseases and infections in childhood. The specific metabolites associated with a reduced disease risk in children may contribute to the characterization of a healthy nutritional profile in pregnancy using a metabolomics‐based unbiased tool for predicting childhood health.